Classification and cyclic fatigue evaluation of new kinematics for endodontic instruments. (16th August 2018) - Gambarini, Gianluca; Piasecki, Lucila; Miccoli, Gabriele; Gaimari, Gianfranco; Di Giorgio, Roberto; Di Nardo, Dario; Azim, Adham A; Testarelli, Luca
Abstract: This study evaluated the effect of new motions of the motor TriAuto ZX2 on the cyclic fatigue of endodontic instruments. Vortex Blue 35.06 instruments were divided into four groups ( n = 10) and tested for fatigue in a curved artificial canal (90° and 2 mm radius) using the following motions: continuous rotation (CR), Optimum Torque Reverse (OTR) set at 180° and the Optimum Glide Path (OGP), which was tested at 90° and 240°. The time to fracture (TTF) and the lengths of the fractured fragments were recorded. The mean TTF was significantly different among the groups (anova, P < 0.05): OGP 90° (213.39 ± 27.45), OTR 180° (121.24 ± 17.03), OGP 240° (45.24 ± 5.61) and CR (8.43 ± 1.27). Weibull analysis confirmed the shortest life expectancy for CR and the longest survival for OGP at 90°. The resistance to fatigue was affected by motions and pre‐set angles. The proprietary movements that are currently available for endodontic instruments were classified according to their kinematics.